Betel nut chewing effects on sustained attention and inhibitory control after sleep deprivation. (12th December 2014) - Ho, Ming‐Chou; Li, Ren‐Hau; Tang, Tze‐Chun
Abstract Objective Betel nut is a common stimulant and addictive substance in Asian countries. We wondered whether chewing betel nut affects sustained attention and inhibitory control after sleep deprivation. Method After one night of deprived or normal sleep, habitual chewers and non‐chewers were asked to complete the sustained attention to response task and the stop‐signal task. Before each task, participants chewed one gum or betel nut. The gum was to control for the effect of mere chewing. In the sustained attention to response task, participants responded to a sequence of numbers on a screen, but to withhold their response whenever they saw the number 3. In the stop‐signal task, they responded to a square or a circle, but withheld their response when a stop signal appeared. Results In the sustained attention to response task, the habitual chewers had lower false alarm rate and longer RT prior to false alarm (particularly when they had normal sleep) than the non‐chewers. In the stop‐signal task, deprived‐sleep participants had longer stop signal reaction time than normal‐sleep participants. Conclusion We reported that the habitual chewers have better sustained attention than the non‐chewers. Also, sleep deprivation weakens inhibitory control. Betel nut chewing does not have an acute effect on either sustained attention or inhibitory control.